Problem-Solving in LCM and GCF Material Using The Project-Based Learning Model Combined with Team-Assisted Individualization and Take and Give - Wijaya, Arinda Oktanthia; Darmiyati, Darmiyati (FKIP ULM, 2024)
This study analyses students' activities, problem-solving skills, and learning outcomes in implementing mathematics learning on LCM (Least Common Multiple) and GCF (Greatest Common Factor) materials using the Project-Based Learning (PjBL) model combined with Team Assisted Individualization (TAI) and Take and Give. This study used classroom action research conducted across four meetings in grade V of SDN Sidomulyo 2 Barito Kuala during the 2023/2024 academic year with 22 students. The research instruments included observation sheets for teacher activity, student activity, problem-solving skills, and student learning outcomes. Data were analyzed using descriptive techniques and presented in tabular form. The results showed that the teacher's activity score increased from 27 in meeting I to 34 in meeting IV. Student activity increased from 40.91% in Meeting I to 95.45% in Meeting IV. Students' problem-solving skills improved from 36.36% in Meeting I to 90.91% in Meeting IV. Student learning outcomes improved, from 40.91% in meeting I to 90.91% in meeting IV. Based on these results, it can be concluded that the PjBL model combined with TAI and Take and Give can significantly improve students' activity, problem-solving skills, and learning outcomes.